Cytoreductive surgery and hyperthermic intraperitoneal chemotherapy for pseudomyxoma peritonei of appendicular and extra‐appendicular origin. (7th February 2018) - Delhorme, J.‐B.; Severac, F.; Averous, G.; Glehen, O.; Passot, G.; Bakrin, N.; Marchal, F.; Pocard, M.; Lo Dico, R.; Eveno, C.; Carrere, S.; Sgarbura, O.; et al.
Abstract : Background: The prognostic value of the primary neoplasm responsible for pseudomyxoma peritonei (PMP) remains poorly studied. The aim of this study was to determine the prognosis for patients with extra‐appendicular PMP (EA‐PMP) treated optimally with complete cytoreductive surgery (CCRS) and hyperthermic intraperitoneal chemotherapy (HIPEC). Methods: All patients treated for PMP with CCRS and HIPEC between 1994 and 2016 were selected retrospectively from a French multicentre database. Patients with EA‐PMP had pathologically confirmed non‐neoplastic appendices and were matched in a 1 : 4 ratio with patients treated for appendicular PMP (A‐PMP), based on a propensity score. Results: Some 726 patients were identified, of which 61 (EA‐PMP group) were matched with 244 patients (A‐PMP group). The origins of primary tumours in the EA‐PMP group included the ovary (45 patients), colon (4), urachus (4), small bowel (1), pancreas (1) and unknown (6). The median peritoneal carcinomatosis index was comparable in EA‐PMP and A‐PMP groups (15·5 versus 18 respectively; P  = 0·315). In‐hospital mortality (3 versus 2·9 per cent; P  = 1·000) and major morbidity 26 versus 25·0 per cent; P  = 0·869) were also similar between the two groups. Median follow‐up was 66·9 months. The 5‐year overall survival rate was 87·8 (95 per cent c.i. 83·2 to 92·5) per cent in the A‐PMP group and 87 (77 to 96) per cent in the EA‐PMP group. The 5‐year disease‐free survival rate was 66·0 (58·7 to 73·4) per cent and 70 (53 to 83) per cent respectively. Conclusion: Overall and disease‐free survival following treatment with CCRS and HIPEC is similar in patients with pseudomyxoma peritonei of appendicular or extra‐appendicular origin. Abstract : Survival similar